Case report: Management of generalized infection and draining tracts of the frontomaxillary region in a dog - Wolfs, Elias; Kot, Ching Ching Shirley; Vapniarsky, Natalia; Arzi, Boaz (Frontiers in Veterinary Science, 2024)
Objective This study aims to report the surgical and medical management of generalized chronic maxillofacial infection with multiple intra- and extraoral draining tracts in a dog. Case summary A 6 years-old, male neutered pit bull terrier dog underwent a staged procedure. First, a diagnostic work-up including hematologic and biochemical analysis, conventional computed tomography (CT) with contrast of the skull, and a rhinoscopic evaluation of the draining tracts was performed. Samples were obtained for histopathological, microbial, and fungal testing. Second, a 4 week course of antimicrobials based on culture and sensitivity results was administered. Third, an extraoral approach to soft tissue reconstruction was accomplished as a first stage in the repair process. Finally, an intraoral approach to repair the oronasal fistulous draining tracts was performed. A 6 months follow-up skull CT revealed various stages of repair and remodeling and adequate soft tissue healing. Clinical relevance A staged procedure is a suitable option to treat chronic and generalized frontal and maxillary infection with multiple intra- and extraoral fistulous draining tracts in dogs.